2012
DOI: 10.1590/s0100-29452012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Especificidade alimentar: em busca de um caráter taxonômico para a diferenciação de duas espécies crípticas de cochonilhas do gênero Planococcus (Hemíptera: Pseudococcidae)

Abstract: fEEding spEcificitY: sEarching a taxonomic charactEr for thE diffErEntiation of tWo crYptic spEciEs of mEalYbugs of thE gEnus PLANOCOCUS (hEmiptEra: psEudococcidaE) abstract-The aim of this study was to investigate a possible host specificity of two cryptic species of mealybugs of the genus Planococcus, reflected in its development in fruits of cocoa, coffee and citrus. The mealybugs Planococcus minor were obtained from cocoa fruits (Theobroma cacao L. cv. Comum) and citrus mealybug, Planococcus citri, from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…pest (Santa-Cecília et al, 2002, 2009) and is occasionally found in citrus Citrus sp. (Corrêa et al, 2005;Sousa et al, 2012) and vineyards Daane et al, 2012). Pl.…”
Section: Discussionmentioning
confidence: 99%
“…pest (Santa-Cecília et al, 2002, 2009) and is occasionally found in citrus Citrus sp. (Corrêa et al, 2005;Sousa et al, 2012) and vineyards Daane et al, 2012). Pl.…”
Section: Discussionmentioning
confidence: 99%
“…In C. arabica, several researches on the development and reproduction of these insects were carried out in Brazil (Correa et al, 2011;Santa-Cecília et al, 2009;Oliveira, 2013;Sousa et al, 2012;Costa et al, 2016). Different periods of development and reproduction of both mealybug species in these coffee plants are found in these literature but laboratory results are difficult to compare due to different experimental conditions, manipulation and above all, the host plant and the plant organ used.…”
Section: Olfactometrymentioning
confidence: 99%
“…A nivel mundial, los insectos escama constituyen un importante grupo de plagas del café (Coffea spp.) (James 1935;Le Pelley 1973;Watson y Cox 1990;Culik et al 2006;Barrera 2008;Sousa et al 2012). En Colombia, desde 1930 se consideran el segundo grupo más importante de insectos plaga en este cultivo (Federación Nacional de Cafeteros 1932), destacándose Puto antioquensis (Murillo, 1931) (Putoidae) y Planococcus citri (Risso, 1813) (Pseudococcidae).…”
Section: Introductionunclassified